2023
DOI: 10.1039/d2cc06936a
|View full text |Cite
|
Sign up to set email alerts
|

Oxoammonium salt-promoted diverse functionalization of saturated cyclic amines with dinucleophiles

Abstract: Oxoammonium salt-promoted diverse functionalization of saturated cyclic amines with different dinucleophiles under mild conditions is presented. To be specific, when thiocyanate was used as 1,3-dinucleophile, hexahydrothiazolo[4,5-b]pyridin-2(3H)-ones were formed via the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…On these bases, it was envisioned to invert the polarity at the C3 position of piperidine 3 (and related N -heterocycles) to incorporate a suitable carbon-based nucleophile . Accordingly, it was hypothesized that with the action of a base, it could simultaneously mediate the deamination process of 4a to C and the formation of phosphorus ylide F from phosphonium salt D , to carry out olefination at C3 of C .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On these bases, it was envisioned to invert the polarity at the C3 position of piperidine 3 (and related N -heterocycles) to incorporate a suitable carbon-based nucleophile . Accordingly, it was hypothesized that with the action of a base, it could simultaneously mediate the deamination process of 4a to C and the formation of phosphorus ylide F from phosphonium salt D , to carry out olefination at C3 of C .…”
Section: Resultsmentioning
confidence: 99%
“…On these bases, it was envisioned to invert the polarity at the C3 position of piperidine 3 (and related N -heterocycles) to incorporate a suitable carbon-based nucleophile. 7 Accordingly, it was hypothesized that with the action of a base, it could simultaneously mediate the deamination process of 4a to C and the formation of phosphorus ylide F from phosphonium salt D , to carry out olefination at C3 of C . Since this entire chemical transformation is planned to be performed under a tandem fashion, we propose that this chemical transformation could be termed as a Wittig-like olefination of a C(sp 3 )–O bond from 4a .…”
Section: Resultsmentioning
confidence: 99%
“…1e) showed that SO 2 release from copperas started at roasting temperatures of above 400 °C, and the released SO 2 concentration increased significantly above 600 °C, reaching a strong peak of 3897 ppm at around 640 °C, and then decreased to 266 ppm at 800 °C, due to the decompositions of FeSO 4 and the intermediate product Fe 2 (SO 4 ) 3 . 24,26,27 However, when copperas and LCO were mixed and roasted at a mass ratio of 1.4 : 1 (stoichiometric molar ratio), the SO 2 emitted by copperas was almost completely eliminated, which may be due to the migration of sulfur from FeSO 4 to Li 2 SO 4 without emitting into the atmosphere. During the holding at 800 °C, the copperas alone condition still released a small amount of approximately 100 ppm of SO 2 gas, whereas the mixture of copperas and LCO exhibited minimal SO 2 emissions.…”
Section: Thermodynamics Feasibility Of Selectively Recovering Lithiummentioning
confidence: 99%